2010
DOI: 10.1128/jvi.00276-10
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Human Immunodeficiency Virus Type 1 Recombination Ex Vivo Provide Evidence for Coadaptation of Distant Sites, Resulting in Purifying Selection for Intersubtype Recombinants during Replication

Abstract: High-frequency recombination is a hallmark of HIV-1 replication. Recombination can occur between two members of the same subtype or between viruses from two different subtypes, generating intra-or intersubtype recombinants, respectively. Many intersubtype recombinants have been shown to circulate in human populations. We hypothesize that sequence diversity affects the emergence of viable recombinants by decreasing recombination events and reducing the ability of the recombinants to replicate. To test our hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 47 publications
(54 reference statements)
3
36
0
Order By: Relevance
“…Surprisingly, the gag hot/cold spots identified in our study match closely with those identified by analyzing patient sequences (6,9,61). This is surprising, because regions of sequence similarity are presumed to drive intersubtype recombination, and one would not expect to see the impact of local recombination hot spots after so many confounding factors, such as selection for functional proteins, drug resistance, or selection from the immune system (9,62). One of the most comprehensive studies, by Simon-Loriere and colleagues, analyzed sequences retrieved from the Los Alamos National Laboratory HIV sequence database (http://www.hiv.lanl.gov) and provides evidence of recombination (9).…”
Section: Discussionsupporting
confidence: 58%
“…Surprisingly, the gag hot/cold spots identified in our study match closely with those identified by analyzing patient sequences (6,9,61). This is surprising, because regions of sequence similarity are presumed to drive intersubtype recombination, and one would not expect to see the impact of local recombination hot spots after so many confounding factors, such as selection for functional proteins, drug resistance, or selection from the immune system (9,62). One of the most comprehensive studies, by Simon-Loriere and colleagues, analyzed sequences retrieved from the Los Alamos National Laboratory HIV sequence database (http://www.hiv.lanl.gov) and provides evidence of recombination (9).…”
Section: Discussionsupporting
confidence: 58%
“…Instead, many recombination events yield dysfunctional proteins that are presumably strongly selected against under natural infection conditions. In addition, the probability that a recombinant is functional varies significantly with the position at which recombination occurs within a gene (14,43). The clustering of breakpoints, as observed in natural group M HIV-1 recombinants, appears to be linked to the structure of the encoded protein.…”
Section: Resultsmentioning
confidence: 99%
“…A pair of recent studies focusing on intersubtype HIV-1 group M recombination emphasized that breakpoints falling within certain regions of env or pol yield chimeric proteins that have a higher probability of being dysfunctional than when breakpoints occur in other parts of these genes (14,43). In the case of env, two factors-the mechanistic tendency for recombination to occur more frequently at certain genome sites and selection against dysfunctional recombinants-were shown to account almost entirely for recombination patterns observed in naturally sampled sequences (43).…”
mentioning
confidence: 99%
“…The degree to which such recombination is deleterious is expected to increase with both decreasing parental relatedness and the extent to which transferred genome sequences interact with other viral genome sequences (12,16,17). Specifically, it is apparent that viral genome regions that have few genetic interactions with other viral genome regions tend to continue functioning better in foreign genetic backgrounds than do those with extensive interaction networks (12,(18)(19)(20).…”
mentioning
confidence: 99%